Peran Dukungan Sosial Masyarakat terhadap Stigma pada Penyintas COVID-19 - Sari, Silvi Fatmala; Isni, Khoiriyah (Perilaku dan Promosi Kesehatan : Indonesian Journal of Health Promotion and Behavior, 2024)
Background. COVID-19 continues to kill people in Indonesia. One of the reasons for the rise in COVID-19 cases is the stigma experienced by COVID-19 survivors and their families in Bumi Jawa Village, Batanghari Nuban District, East Lampung Regency, Lampung Province. The kind of stigma received includes rejection of self-isolation, a lack of community empathy, and social support during the isolation phase. Objective. The purpose of this study is to assess the impact of community social support on community stigma toward COVID-19 survivors in Bumi Jawa Village, Batanghari Nuban District, East Lampung Regency, Lampung Province. Method. This study is a cross-sectional, analytical observational study. Purposive sampling was employed with 60 COVID-19 survivors who met the inclusion and exclusion criteria, and the data was analyzed using the chi-square test. Results. There is a relationship between each component of social support in the attachment community (p-value= 0.03), social integration (p-value=0.001), reassurance of worth (p-value=0.001), reliable alliance (p-value=0.001), guidance (p-value=0.00`) in reducing stigma among COVID-19 survivors in Bumi Jawa Village. There is no relationship between opportunity for nurturance and stigma.